2012
DOI: 10.1111/j.1532-7078.2012.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Reactivity to Infant Crying and Observed Maternal Sensitivity

Abstract: Relations between maternal sensitivity and physiological reactivity to infant crying were examined using measures of heart rate (HR) and respiratory sinus arrhythmia (RSA) in 49 mothers of second‐born infants. Using the Ainsworth Sensitivity Scale, an independent assessment of maternal sensitivity was made during maternal free play and bathing of their infants. Physiological reactivity was measured while mothers listened to three blocks of infant cry sounds in a standard cry paradigm. Mothers scoring high on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
86
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 52 publications
(83 reference statements)
13
86
1
2
Order By: Relevance
“…This demonstrates that results are difficult to compare when different operationalizations of parenting are used. Our results support the basic notion that ANS arousal is a requirement for sensitive parenting, for which promptness of response is a main condition [27]. Congruently, in a sample of mothers where normative, hyper-, and hypoarousal patterns of the ANS were distinguished during the Strange Situation, mothers showing autonomic hypoarousal scored highest on observed insensitive parenting behavior [28].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This demonstrates that results are difficult to compare when different operationalizations of parenting are used. Our results support the basic notion that ANS arousal is a requirement for sensitive parenting, for which promptness of response is a main condition [27]. Congruently, in a sample of mothers where normative, hyper-, and hypoarousal patterns of the ANS were distinguished during the Strange Situation, mothers showing autonomic hypoarousal scored highest on observed insensitive parenting behavior [28].…”
Section: Discussionsupporting
confidence: 83%
“…Excluded and included mothers were similar on childhood maltreatment experiences (total CTQ scale), educational level, maternal age, children's mean age, and whether children had a clinical diagnosis (ps [ 27). Table 1 displays characteristics of maltreating mothers and non-maltreating mothers.…”
Section: Preliminary Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this early detection in brainstem regions might support initiation of a state of heightened physiological arousal upon detection of infant cues. Peripheral psychophysiological studies have demonstrated that hearing infant cries can impact the listener's heart rate, respiration and hand grip strength [although the direction of these effects varies across studies; [72,[73][74][75][76][77]]. It is hypothesised that heightened physiological arousal aids the initiation of rapid, effortful caregiving behaviour.…”
Section: Early Detection Of Infant Vocalisations In the Brainstemmentioning
confidence: 99%
“…Anyone who has experienced the presence of a child suffering with an illness such as colic can wholeheartedly agree that the behaviors of the infant negatively impact all participants near the child. Research indicates the vocalization of the distress of an infant significantly impact all adults within hearing, both physiologically and psychologically [6][7][8]. Therefore, it is plausible that the presence of a child experiencing an exceptionality may have a mediating effect on IPV.…”
Section: Introductionmentioning
confidence: 99%